A Critical Juncture: “Later” Latin Literature, the Newest Late Antiquity, and the Period of the Western Classic - Mark Vessey (Journal of Latin Cosmopolitanism and European Literatures, 2022)
With the appearance in 2020 of a long-awaited second “late antique” instalment of the Handbuch der lateinischen Literatur der Antike (Munich: C.H. Beck, 1989– ) and a new, collaborative Cambridge History of Later Latin Literature now at an advanced stage of preparation, there is an opportunity to re-evaluate the possibilities of scholarship in this field. What relation does such “literary” research bear to current, globalizing styles in late antique and first-millennial historical and cultural studies? What is likely to be the impact on it of current trends in the study of classical reception and intertextuality? This essay attempts a preliminary framing of the issues with reference to a largely discredited but still powerful model of the western literary classic, while arguing for hermeneutical continuity between the breakthrough work of Peter Brown’s half-century-old World of Late Antiquity (1971) and the critical-historical role of later ancient (Latin) literary studies.